Numerical Investigation On The Strengthening Work Of Transmission Tower - Jamberi, Aqilah (Universiti Sains Malaysia, 2017)
Windstorm occurrence in Malaysia is unpredictable as the world becomes old. The susceptibility in designing structures under wind storm is important to ensure no damages occurs which leads many negative impacts mostly towards the society. Therefore, an upgrading the transmission tower is important nowadays to overcome this wind disaster. Basically, the method on retrofitting of existing transmission tower is by adding the horizontal braces or as known as diaphragm or by secondary member. In this study, the critical member in each panelise been identify and the most effective type of diaphragm is being introduce through multiple analysis. Four types of diaphragm are introduced in this study. The results shown that, diaphragm type A is the most efficient as it can carry the same load with the minimize steel weightage. Lattice structure need to be upgrading by adding the diaphragm to eliminate the failure members. Diaphragm type A gave the lowest additional steel weightage with zero number of failed member. Hence, the most economical method was produced with a reduction on its used capacity.